BUSINESS OF PRODUCTION OF PANDAN MAT AND LOPAK MAT: IN LENGKOK LENDANG, TEMBENG PUTEK VILLAGE: A LITERATURE PERSPECTIVE: BISNIS PRODUKSI TIKAR PANDAN DAN TIKAR LOPAK : DI DUSUN LENGKOK LENDANG DESA TEMBENG PUTEK: A LITERATURE PERSPECTIVE - Indrayanti Andi (Journal of Business Issues, 2022)
Craft mats should be preserved and sustainable considering that handicraft is one of the ancestral heritages that can improve the community's welfare, and their uniqueness can attract the attention of domestic and foreign tourists. However, the welfare gap received by the artisans can threaten the sustainability and existence of the two mat crafts. Based on a literature study, it is concluded that in improving the welfare of artisans in Indonesia, with a case study on mat artisans in Lengkok Lendang, Tembeng Putek Village, they must be guided to continue implementing the feasibility study. Through their SME forum, the artisans must maintain good market and marketing aspects but must make improvements to several things in terms of the business environment and financial aspects. To overcome impropriety in marketing, business, environmental, and financial aspects, it is necessary to build a joint forum to strengthen the role of SMEs in digitally marketing these mat products by displaying prices that are in line with their quality and aesthetics.